2014
DOI: 10.1097/mlr.0000000000000069
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Refill Function Through an Online Patient Portal is Associated With Improved Adherence to Statins in an Integrated Health System

Abstract: Background Online patient portals are being widely implemented, but their impact on health behaviors are not well-studied. Objective To determine whether statin adherence improved after initiating use of the portal refill function. Research Design Observational cohort study within an integrated healthcare delivery system. Subjects Diabetes patients on statins who had registered for online portal access by 2010. 8,705 subjects initiated online refill function use within the study window, including “exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 35 publications
1
87
0
1
Order By: Relevance
“…While the evidence is far from conclusive, studies do suggest that patient portals can improve processes of care and adherence. 3,4 Technology is also thought to benefit health through improved patient activation and selfmanagement achieved via access to online health information and peer support. 5,6 However, clear and consistent evidence related to health disparities is lacking.…”
mentioning
confidence: 99%
“…While the evidence is far from conclusive, studies do suggest that patient portals can improve processes of care and adherence. 3,4 Technology is also thought to benefit health through improved patient activation and selfmanagement achieved via access to online health information and peer support. 5,6 However, clear and consistent evidence related to health disparities is lacking.…”
mentioning
confidence: 99%
“…[6][7][8] One study suggested that patient use of an online portal with refill function increased adherence to statin medications for those with diabetes receiving care in an integrated health system. 9,10 Studies also report that low education, income, and Internet access are associated with lower online use of an SMR, though socioeconomic status (SES) alone does not account for lower SMR use by racial-ethnic minorities. 11 African Americans and Latinos are less likely to use an online SMR system that has options to request medication refills.…”
Section: Introductionmentioning
confidence: 99%
“…174 The impact of patient portals on health is largely unknown, but in one report, use was associated with greater adherence to statins and lower low-density lipoprotein levels. 175 Together, these new technologies and new approaches reveal a shift in our appreciation for the value of patientcollected data obtained outside the conventional clinic setting. In addition, there is growing recognition among funders that research into this area is needed.…”
Section: Patient-reported Informationmentioning
confidence: 99%